AICCRA validation report: Piloting and validating the Climate Security Sensitivity Scoring Tool (CSST): Evidence from the field on the climate security sensitivity of the climate smart village approach in Jirapa, Ghana. - Sarzana, Carolina; Mahama, George; Jaquet, Stéphanie (2023)
A one-day workshop in Jirapa, Ghana was organized to test the results of the Climate Security Sensitivity Tool (CSST) and reflect on the reliability of its recommendations. This document reports on the results of the CSST piloted on the Climate Smart Village (CSV) approach implemented in Jirapa and on the outcomes of the workshop that reflected upon these results and recommendations. The CSST results showed that while the CSV contributed to several peace co-benefits, certain aspects of the program could have been further enhanced to increase its conflict sensitivity and peace responsiveness, particularly regarding institutional capacities building. The workshop validated the drivers of conflict and insecurity flagged by the CSST, emphasizing that the drivers in the Jirapa region were more significant than at the national level. They stressed the importance of economic development, enhancing knowledge, building institutions, resource sustainability, building capacity and resilience, and building trust and cooperation in addressing these challenges. The workshop's outcomes validated the CSST's utility and demonstrated that the tool can provide suitable recommendations when coupled with localized insights, enhancing its value in crafting context-specific climate adaptation programs that effectively address the drivers of conflict and insecurity in vulnerable regions. One key revelation from the workshop is the limitation of using generalized risk indicators at country level.